Design and characterization for dual-band and multi-band A-sandwich composite radome walls. (8th September 2017) - Zhou, Licheng; Wang, Peiyu; Pei, Yongmao; Zeng, Anmin; Tang, Liqun; Liu, Zejia; Liu, Yiping; Jiang, Zhenyu; Fang, Daining
Abstract: Nowadays, radomes that are employed to protect antennas inside from physical environment are required to have dual-band or even multi-band transmission performance. In this paper, a design scheme based on the theory of small reflections is proposed for the design of dual-band and multi-band A-sandwich radomes. Subsequently, two A-sandwich composite radome walls are designed and fabricated according to the design scheme. Finally, both numerical simulations and experiments are conducted to verify the electromagnetic characteristics of the radome walls. Results indicate that one of the A-sandwich radome walls has two passbands in 4.0–11.4 GHz and 25.2–40.0 GHz, while the other one has three passbands in 4.0–8.2 GHz, 18.0–20.5 GHz, and 29.1–40.0 GHz, respectively. The proposed method is experimentally demonstrated to be an effective approach for designing dual-band and multi-band dielectric radome walls for both centimeter and millimeter wave applications.